Clinical Scoring Systems in Thrombotic Microangiopathies - Bendapudi, Pavan K.; Upadhyay, Vivek; Sun, Lova; Marques, Marisa B.; Makar, Robert S. (Seminars in Thrombosis and Hemostasis, 2017)
Thrombotic microangiopathies (TMAs) are a group of rare but potentially lethal hematologic disorders characterized by platelet-rich thrombi in the microvasculature. In evaluating patients with TMA, it is crucial to identify those who have thrombotic thrombocytopenic purpura (TTP), a subtype of TMA that occurs due to a severe deficiency in ADAMTS13 (adisintegrin and metalloprotease with thrombospondin type 1 motif, member 13). Individuals with TTP require urgent therapeutic plasma exchange, which is associated with a significant reduction in mortality; however, at most centers, the results of ADAMTS13 activity testing are usually not available for 3 to 5 days. Given the possible need for urgent intervention and the lack of timely test results to guide therapy, the assessment of patients with TMA represents an ideal situation for the deployment of diagnostic scoring systems to predict the presence of severe ADAMTS13 deficiency. Here, we review the literature surrounding clinical prediction tools in the diagnosis and prognostication of patients with TMA, describe the experience at our center with evaluating TMA patients, and discuss the utility of clinical scoring systems for TMA in the context of patient care.
Keywords: thrombotic microangiopathy; clinical scoring system; prediction tool; thrombotic thrombocytopenic purpura; treatment recommendations